THE EFFECT OF COLEUS TUBEROSUS CONTAINING RESISTANT STARCH TYPE 3 CRACKERS ON HYPERCHOLESTEROLEMIA SUFFERING ANIMALS - Mutiara Nugraheni; Siti Hamidah; Rizqie Auliana (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2016)
This study was aimed at determining the effect of Coleus tuberosus containing resistant starch type 3 on the hypercholesterolemia suffering animals. The research method used was lipid proﬁ le analysis on experimental animals suffering from hypercholesterolemia. The results showed that the consumption of Coleus tuberosus crackers containing resistant starch type 3 as a raw material for making crackers is able to decrease the lipid proﬁ le (total cholesterol, triglycerides, LDL) and increase the HDL level.